Women, Consumption, and the Circulation of Ideas in South-Eastern Europe, 17th - 19th Centuries - Vintilă-Ghiţulescu, Constanţa (Balkan Studies Library, 2017)
Women, fashion, consumption, luxury, and education are the main subjects of our researchers. The contributors of this volume accompanied women and objects in their travels across Modern Europe and offered thorough and diverse analyses connecting the circulation of people with the circulation of ideas. Making use of the archive materials, visual sources and museum collections, the authors pointed out the richness of the region and the role of women in promoting new ideas of modernity. The information contained here will help the public to better know and understand the part of women's sociability in building new nations and constructing new identities along South-Eastern Europe and beyond.